2021
DOI: 10.4103/jpbs.jpbs_676_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Marginal Bone Loss and Implant Failure Rate in Smokers and Nonsmokers

Abstract: Background: Smoking impose various ill-effects on the alveolar bone concerning dental implants including reduced bone height, delayed healing of bone, poor peri-implant bone formation, increased bone loss, and peri-implantitis. Aims: The present clinical trial was aimed to analyze the smoking effect on dental implant survival rate as well as marginal bone loss in dental implants. Materials and Methods: Out of 86 patients, Group I had 43 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…However, rough implant surfaces are associated with many risks, including complications, peri-implant infections, and increased marginal resorption, as evidenced by previous literature data. For the posterior maxilla, bone augmentation can be replaced by sinus membrane lift during simultaneous implant placement without bone grafts [ 10 ]. This clinical study aimed to clinically and radiographically assess the healing of endosseous implants having different surface characteristics in nongrafted and grafted bone.…”
Section: Introductionmentioning
confidence: 99%
“…However, rough implant surfaces are associated with many risks, including complications, peri-implant infections, and increased marginal resorption, as evidenced by previous literature data. For the posterior maxilla, bone augmentation can be replaced by sinus membrane lift during simultaneous implant placement without bone grafts [ 10 ]. This clinical study aimed to clinically and radiographically assess the healing of endosseous implants having different surface characteristics in nongrafted and grafted bone.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have generally demonstrated that smokers have less favorable healing in response to both non-surgical and surgical periodontal therapy [ 38 , 39 , 40 , 41 , 42 ] and they may also respond differently to peri-implant disease therapy. In fact, the negative effects of smoking on wound healing are mainly caused by chemical substances as nicotine, carbon monoxide, hydrocyanic acid, and nitrogen oxide [ 43 ], but the exact mechanisms by which tobacco exerts its influence on healing and more generally on the health of periodontal tissues are not completely elucidated and could be influenced by multiple factors [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%